2002
DOI: 10.1021/jf011505r
|View full text |Cite
|
Sign up to set email alerts
|

Maturing Wines in Oak Barrels. Effects of Origin, Volume, and Age of the Barrel on the Wine Volatile Composition

Abstract: The influence of the oak origin, volume, and age of the barrel on the volatile composition of a red wine after six months of maturation have been studied. Major volatile compounds in wine were determined using liquid-liquid extraction with dichloromethane, and those volatiles being due to the oak were determined by extraction with pentane-ether using deuterated analogues as internal standards. The results show that there is little difference between the volatile composition of wines matured in French oak barre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 20 publications
4
74
0
Order By: Relevance
“…The cider aged with the American oak chips had the highest concentration of vanillin among the three treatments (Table III). Similar results have been reported by other authors 18,20 , although some researcher found that vanillin levels were higher in the wines matured in French oak barrels 24,28 .…”
Section: Effect Of the Geographical Origin Of Oak Chipssupporting
confidence: 91%
See 4 more Smart Citations
“…The cider aged with the American oak chips had the highest concentration of vanillin among the three treatments (Table III). Similar results have been reported by other authors 18,20 , although some researcher found that vanillin levels were higher in the wines matured in French oak barrels 24,28 .…”
Section: Effect Of the Geographical Origin Of Oak Chipssupporting
confidence: 91%
“…A total of 100 mL of each cider, spiked with 2-octanol (IS) to a final concentration of 0.02 mg/L, in a 250 mL spherical flask with 20 mL of freshly redistilled dichloromethane, was extracted by means of ultrasound over 20 min at 20°C 24 . The organic phase was saved in a flask.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%
See 3 more Smart Citations